The Role of Metagenomic Next-Generation Sequencing as a Promising Technology for Diagnosing HIV-TB Coinfection - Zhonghui Liao; Sumei Yang; Qian Li; Hongzhou Lu (Zoonoses, 2022)
The human immunodeficiency virus (HIV) pandemic has caused a resurgence of tuberculosis (TB), thus increasing morbidity and mortality. Moreover, HIV-TB coinfection leads to difficulties in diagnosis. Sputum smear microscopy, mycobacterial culture and GeneXpert MTB/RIF assays are generally endorsed to detect Mycobacterium tuberculosis ( M. tuberculosis ) in HIV-TB coinfection. However, these methods cannot diagnose TB in an accurate and timely manner, thus increasing the rates of HIV-associated morbidity and mortality in patients with TB. Hence, a considerable need exists for better diagnostic tools for patients with HIV-TB coinfection. Metagenomic next-generation sequencing (mNGS) is a novel detection platform widely used to assess infectious disease, antimicrobial resistance, the microbiome and human host gene expression. Herein, we summarize the advantages of mNGS for infectious disease diagnostics. We then assess the efficiency of mNGS in the detection of M. tuberculosis in different specimens and several cases of HIV-TB coinfection. We conclude that mNGS is an acceptable diagnostic method for HIV-TB coinfection, although limited research is available.